Searching PubMed for a broad subject area: how effective are palliative care clinicians in finding the evidence in their field?. (21st August 2015) - Damarell, Raechel A.; Tieman, Jennifer J.
Abstract: Objectives: Health professionals must be able to search competently for evidence to support practice. We sought to understand how palliative care clinicians construct searches for palliative care literature in PubMed, to quantify search efficacy in retrieving a set of relevant articles and to compare performance against a Palliative CareSearch Filter (PCSF). Methods: Included studies from palliative care systematic reviews formed a test set. Palliative care clinicians ( n  = 37) completed a search task using PubMed. Individual clinician searches were reconstructed in PubMed and combined with the test set to calculate retrieval sensitivity. PCSF performance in the test set was also determined. Results: Many clinicians struggled to create useful searches. Twelve used a single search term, 17 narrowed the search inappropriately and 8 confused Boolean operators. The mean number of test set citations ( n  = 663) retrieved was 166 (SD = 188), or 25% although 76% of clinicians believed they would find more than 50% of the articles. Only 8 participants (22%) achieved this. Correlations between retrieval and PubMed confidence (r = 0.13) or frequency of use ( r  = −0.18) were weak. Conclusions: Many palliative care clinicians search PubMed ineffectively. Targeted skills training and PCSF promotion may improve evidence retrieval.